(untitled) (Research, Society and Development, 2022)
Raynaud’s Syndrome (RS) is generally characterized by either ischemic or hyperemic symptoms and is relatively frequent in patients hypersensitive to cold or with emotional stress. This phenomenon usually cease after no more than some minutes, however, can persist for hours Its treatment is aimed at promoting vasodilation i.e., warming procedures. Anxiety control prior to surgical procedure helps in prevention the occurrence of RS. Despite RS following local dental anesthesia being rare, dentists must be prepared to manage. There are limited reports of patients with this syndrome during dental procedures, so here we describe a case of a patient who has undergone a surgical implant installation and who developed primary RS following local anesthesia using an adrenergic vasoconstrictor, as well as the management of this complication in dental office. Dentists should be able to recognize the RS and follow the appropriate guidelines available, after control the case the patient should also be referred to a general physician for further investigations.